Pelatihan Profitabilitas Produksi Lampu Hias Berbahan Limbah di Ranting Aisyiyah Kedungpeluk - Dias Agustiningrum; Indra Lesmana; Nela Akhmalia; Reza Aulia Windari (Jurnal Pengabdian kepada Masyarakat Nusantara, 2023)
The purpose of this service is to produce products in the form of decorative lamps and profitability in Aisyiyah Kedungpeluk Branch. The development of crafts to make dimmer lamps is an effort to utilize used goods in the form of paralon and shells to become attractive and useful items. This method uses 3R 9Reduce, reuse, and recycle) so that it can minimize the production of plastic waste that can pollute the environment and expand the creativity of IPM children. As well as being able to increase community income and reduce unemployment which results in a decrease in the community's economy. Increasing people's income can help the economic growth of the aisyiyah branch to be more developed in the future.  Assistance and introduction to the processing of plastic waste independently using graphic design methods in order to make quality products and make profitability for welfare. The goal to be achieved is that people can utilize used goods properly and usefully.